Análise histomorfométrica após ação do campo magnético no processo de reparo ósseo em coelhos - Silva, Daniel Ferraz Nunes da (2018)
The objective of this study was to evaluate the repair of bone defects surgically created, filled with blood clot and submitted to permanent and constant magnetic stimulation in rabbit calvaria using histomorphometric analysis. Twenty-four New Zealand rabbits, albino, male, young adults, about seven months of age were included in the experimental research. After adequate exposure of the parietal bones, two 1 cm diameter ostectomies were made for bone defects and stores for the insertion of the magnets (test group - CMP) or titanium metallic devices (control group - CMA). The magnets or metal devices were fixed at 1.0mm distance from the defects, following an imaginary line that cut the defect longitudinally at its largest diameter. The defect used in the study was that of the left side that was kept only by clot. The animals were submitted to euthanasia at 30 and 60 days postoperatively. The obtained sections were stained with hematoxylin and eosin (HE) for the histomorphometric analysis of the formed bone area (AO) inside the defect. The results were presented through averages and standard deviations of the percentage of bone neoformation for the histological analysis. Data were submitted to the Kolmogorov-Smirnov normality test. Then, intragroup and intergroup comparisons were performed using the One-Way ANOVA statistical test for the comparison of μm2 micrometer, with a significance level of 5%. In cases where there was a statistically significant difference, the Dunn test was applied. All statistical tests, appropriate to the experiments, groups and values obtained were applied through the SIGMA STAT program. The results showed that there was a significant intragroup difference (CMP group with p = 0.008) in which at 30 days the mean bone neoformation was 81,89 micrometer μm2 (standard deviation ± 18.2) and 12.8 micrometer 12.8 μm2 (standard deviation ± 4.8) at 60 days. In intragroup analysis of the CMA group this difference was not verified. In the intergroup analysis there was no significant difference in the analyzed periods. The magnetic field evaluated in the present study accelerated the bone repair in defects surgically created in the initial period of the process.